2017
DOI: 10.1080/13548506.2017.1344253
|View full text |Cite
|
Sign up to set email alerts
|

Age stereotypes, flexible goal adjustment, and well-being among Chinese older adults

Abstract: Previous studies have examined the independent roles of positive age stereotypes (PAS) and negative age stereotypes (NAS) in successful aging. This study aimed to examine the joint effect of PAS and NAS on the well-being of Chinese older adults, and to further examine whether this effect was moderated by flexible goal adjustment (FGA). Using a cross-sectional design, 279 Chinese older adults (age range 60‒97 years) completed measures related to age stereotypes, FGA, and well-being. The results showed that PAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…FGA implies that individuals pursue their own personal goals, disengaging from goals that are incompatible with their preferences and altering their goals in response to unique conditions. Zhang et al (2018) found that the interaction term, including FGA, was significant in predicting well-being ( β = .19, p < .01). Negative age stereotypes decreased the positive effect of positive age stereotypes on well-being for older adults with low FGA conditions, but the effect remained the same for individuals with high FGA.…”
Section: Resultsmentioning
confidence: 93%
“…FGA implies that individuals pursue their own personal goals, disengaging from goals that are incompatible with their preferences and altering their goals in response to unique conditions. Zhang et al (2018) found that the interaction term, including FGA, was significant in predicting well-being ( β = .19, p < .01). Negative age stereotypes decreased the positive effect of positive age stereotypes on well-being for older adults with low FGA conditions, but the effect remained the same for individuals with high FGA.…”
Section: Resultsmentioning
confidence: 93%
“…Compared with the three-factor model of the FTPS in Rohr et al’s study (2017), Cate and John’s (2007) two-factor model was better supported in this study. The different analysis strategies (confirmatory factor analysis in this study and exploratory structural equation modeling in Rohr et al’s [2017] study) and sample characteristics (younger age in Rohr et al’s [2017] study) might have led to the inconsistent factor structure of the FTPS.…”
Section: Discussionmentioning
confidence: 90%
“…Participants were asked, “When you think of old people in general, how closely do these words match the images or pictures that you have?” Items were rated on a 7-point Likert-type scale ranging from 0 ( does not match at all ) to 6 ( completely matches ). This measure showed good psychometric properties in Chinese older adults (Zhang, Yu, Zhang, & Zhou, 2018). Positive age stereotypes and negative age stereotypes are two distinct dimensions of this measure (Levy et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Participants indicated their response on a 5-point Likert-type scale, ranging from 1 (strongly disagree) to 5 (strongly agree). This measure showed good psychometric properties for Chinese older adults (Zhang, Yu, Zhang, & Zhou, 2018). Higher scores on the TGP Scale and FGA Scale indicated higher levels of TGP (a h ¼ .70; a w ¼ .63) and FGA (a h ¼ .70; a w ¼ .64), respectively.…”
Section: Methodsmentioning
confidence: 94%
“…Participants rated each word on a 7-point Likert-type scale, ranging from 0 (does not match at all) to 6 (completely matches). This measure showed good psychometric properties for Chinese older adults (Zhang et al, 2018). Higher scores on this scale indicated more PSA (Cronbach's a coefficient for husbands, a h ¼ .83; Cronbach's a coefficient for wives, a w ¼ .78).…”
Section: Methodsmentioning
confidence: 95%